Peran Leadership Dalam Mengelola Sumber Daya Manusia Yang Berkualitas - Mukaromah Syakoer (CV. ULIL ALBAB CORP, 2023)
Human resources are one of the crucial factors that can determine the growth and success of an organization. The quality of human resources is a component that needs careful attention in an organization and is closely related to the role, position, and function of leadership in the organization. Leadership with a focus on principles and professional values easily guides an organization to grow and develop in line with its vision and mission. Additionally, leadership serves as a vital instrument in an organization. The aim of this research is to understand the role of leadership in managing high-quality human resources (HR). The research methodology employed is a literature review using Google Scholar as tools. The research findings state that leadership plays a crucial role in creating positive changes in building high-quality HR, enhancing the quality of public services, and overall organizational performance.